EFFECT OF MODERATE INTENSITY EXERCISE ON BODY WEIGHT AND BLOOD ESTROGEN LEVEL OVARIECTOMIZED MICE - Prasetya, Rizka Eka; Umijati, Sri; Rejeki, Purwo Sri (Faculty of Medicine, Universitas Padjadjaran, 2018)
Estrogen is a hormone which is related to lipid oxidation, lypogenesis inhibition, and lipolysis rate. The purpose of this study was to determine the effect of moderate intensity exercise on body weight and blood estrogen level in ovarectomized mice (ovx). The study was held in the Laboratory of Biochemistry, Faculty of Medicine Universitas Airlangga during the period of April to May 2017 on old nineteen 3-4 months old female mice, , 20-30 grams of weight, which were divided into two groups: OVX (n=9, ovx without exercise) and OVX+E (n=10, ovx and moderate intensity exercise). Moderate intensity exercise in this study included swimming, three times a week at 3 pm for four weeks using a 6% of body weight load. Experiment data were analyzed by paired t-test and independent t-test using SPSS. The average body weights of the OVX group were 26.44 ± 1.94 grams and 29.89 ± 2.62 gram at pretest and posttest, respectively., while for the OVX+E group, the weights were 26.50 ± 2.59 grams and 26.40 ± 2.07 grams. There were asignificant intergroup body weight differences (?OVX= 3.44 ± 2.55 gram and ?OVX+E= -1.00 ± 1.37 gram) with p=0.004. Blood estrogen level in OVX+E (12.04 ±10.13 ng/ml) was higher than in control (OVX= 11.24 ± 8.33 ng/ml); however, the difference was not significant (p=0.855). Moderate intensity exercise reduces body weight, without any significant increase in blood estrogen level. Hence, the body weight loss is not caused by estrogen, which may be due to the short period of exercise in this study that the estrogen has not had the time to increase.Pengaruh Olahraga Intensitas Sedang terhadap Berat Badan dan Kadar Estrogen Darah pada Mencit Ovariektomi Estrogen merupakan hormon yang berperan pada oksidasi lipid, kecepatan lipolisis, dan hambatan lipogenesis. Penelitian bertujuan mengetahui pengaruh olahraga intensitas sedang terhadap berat badan dan kadar estrogen darah pada mencit ovariektomi (ovx). Penelitian dilaksanakan di Laboratorium Biokimia Fakultas Kedokteran Universitas Airlangga, April?Mei 2017. Sejumlah 19 mencit betina berusia 3?4 bulan, berat 20?30 gram, dibagi menjadi dua kelompok: OVX (n=9, ovx tanpa perlakuan) dan OVX+E (n=10, ovx dengan olahraga intensitas sedang). Olahraga intensitas sedang dilakukan dengan renang, tiga kali seminggu pukul 15.00 WIB selama empat minggu dengan beban 6% dari berat badan. Data dianalisis dengan paired t-test dan independent t-test SPSS. Berat badan OVX pra-tes 26,44±1,94 gram dan pascates 29,89±2,62 gram. Berat badan OVX+E pra-tes 26,50±2,59 gram dan pascates 26,40±2,07. Terdapat perbedaan bermakna berat badan antarkelompok (?OVX= 3,44±2,55 gram and ?OVX+E= -1,00±1,37 gram), p=0,004. Kadar estrogen darah OVX+E (12,04±10,13 ng/mL) lebih tinggi daripada konrol (OVX= 11,24±8,33 ng/mL), tetapi tidak berbeda bermakna (p=0,855). Olahraga intensitas sedang menurunkan berat badan, tetapi tidak bermakna meningkatkan kadar estrogen darah. Penurunan berat badan tidak disebabkan oleh estrogen. Peningkatan estrogen belum terjadi mungin disebabkan oleh waktu yang kurang lama.